Development of Flipbook-Based E-Module to Improve Students’ Learning Outcomes in Basketball Course - Marpaung, Deni Rahman; Ilham, Zulpikar; Marlina, Murni Eva (AL-ISHLAH: Jurnal Pendidikan, 2024)
Limited learning resources for integrating theory and practice in e-module-based physical education, particularly in basketball, present challenges in enhancing student learning outcomes. This study addresses the development and assessment of multimedia-based basketball teaching materials aimed at improving students' understanding and performance in sports education. This research employed a Research and Development (RD) approach with a quantitative design. The developed multimedia basketball game application was evaluated by experts, including basketball coaches and university lecturers from Medan State University, to assess its suitability as a teaching resource. The evaluation process involved both content and media experts. The assessment by basketball learning material experts yielded a score of 87.52%, indicating the application is highly suitable for use in educational settings. Media experts provided a score of 89.70%, further affirming the multimedia basketball application’s effectiveness as a teaching tool. Both evaluations reflect the application’s potential to bridge the gap between theory and practice in basketball education. The findings suggest that the multimedia basketball game application is a viable tool for enhancing basketball education. Its implementation can improve the quality of teaching, support lecturers in delivering complex content, and ultimately enhance students' learning outcomes in sports science. The development of a multimedia-based e-module for basketball is a significant step towards improving the resources available for physical education. The application has been validated by experts and can be effectively integrated into the curriculum to enhance learning in basketball courses.